Pendaftaran Tanah Masyarakat Adat Toraja - Evitasari, Sherly; Syafira, Agina; Saleh, Raden Deden Dani (Sekolah Tinggi Pertanahan Nasional, 2024)
Indigenous communities have a noble tradition and cultural identity for sustainably managing their dwellings and territorial environments. With increasing physical, economic, and social development, indigenous communities face incredible difficulty obtaining recognition and respect for their customary rights from the government. This research aims to highlight the indigenous Tana Toraja community's land and ancestral property management system, which is crucial for recognizing the indigenous Tana Toraja community's land and ancestral property management system, which is essential to realizing their customary rights. Using a qualitative method involving interviews and observations, the study engaged 12 purposively selected informants from two villages in the Tana Toraja Regency. The findings indicate that the Toraja people inherit and manage land and Tongkonan properties as cultural heritage from their ancestors. Land transfer practices consider dedication to parents and contributions to customary ceremonies. The registration process for indigenous land is conducted in the Ulayat land registry, reflecting the land's existence. The findings emphasize that the indigenous community's land and property management system is crucial to their recognition and respect. This underscores the importance of understanding and respecting customary practices in the context of cultural preservation and indigenous rights. Masyarakat adat memiliki tradisi dan identitas budaya luhur dalam mengelola tempat tinggal serta lingkungan teritorialnya secara berkelanjutan. Seiring dengan meningkatnya pembangunan fisik, ekonomi dan sosial, masyarakat adat semakin kesulitan mendapatkan pengakuan dan penghormatan atas hak-hak adatnya dari pemerintah. Penelitian ini bertujuan menyoroti sistem pengelolaan tanah dan harta pusaka Masyarakat Adat Tana Toraja yang penting untuk pengakuan hak adat mereka. Dengan metode kualitatif, melalui wawancara dan observasi, penelitian ini melibatkan 12 narasumber secara purposive dari dua desa di Kabupaten Tana Toraja. Hasil penelitian menunjukkan bahwa Masyarakat Toraja mewarisi dan mengelola tanah serta properti Tongkonan sebagai warisan budaya dari nenek moyang mereka. Praktik pengalihan tanah dilakukan dengan mempertimbangkan pengabdian kepada orang tua dan kontribusi pada upacara adat. Proses pendaftaran tanah adat dilakukan pada daftar tanah ulayat, mengikuti keberadaan tanahnya. Temuan menekankan bahwa sistem pengelolaan tanah dan harta masyarakat adat merupakan kunci untuk pengakuan dan penghormatan terhadap mereka. Hal ini menunjukkan pentingnya memahami dan menghargai praktik adat dalam konteks perlindungan budaya dan hak-hak masyarakat adat.